From Fashion Brand to Artwork: Divergent Thinking, Copyright Law, and Branding - Marlena Jankowska; Berenika Sorokowska (Laws, 2023)
The purpose of this study is to explore the interaction between copyright, branding, marketing, and heritage protection with regard to a fashion brand. The authors use analytical-critical and legal-dogmatic methods, supplemented with desk research, a case study approach, and a review of the marketing literature. This paper argues that the top-tier fashion brands use the concept of artification in order to build their brands, mesmerize clientele, and increase revenues. Although design and reference to the arts play a major role in the luxurious and premium end of the fashion business, this analysis proves that the top players do not necessarily observe the appropriate laws in these areas. The reader will see examples of the flouting of basic legal constraints by big players, e.g., copyrights or property rights, including the monetisation of the creativity of others with the expectation of no legal challenge. Offenders capitalise on the likelihood that a legal suit is too demanding for smaller players, such as foundations or museums.